2020
DOI: 10.5958/0974-360x.2020.00347.9
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dissolution Rate of Piperine by Multicomponent Crystal Formation with Saccharin

Abstract: Piperine, a secondary metabolite of Piper nigrum L., has been known for its pharmacological activities. However, the use of piperine is still limited due to the low solubility in water. The aim of this study was to improve the physicochemical properties of piperine by preparing into multicomponent crystal (MC) using saccharin by solvent evaporation method, and ethanol was used as the solvent. The intact materials and MC were characterized by several solid-state instruments. The amount of dissolved piperine was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The most commonly used technique for preparing phytochemical MCCs using the solution-based method is solvent evaporation (Katherine et al, 2018;Setyawan et al, 2018;Zaini et al, 2020b), in which the API and coformer are dissolved with a suitable solvent and the solvent is then allowed to evaporate slowly at room temperature (Kumar, 2018) . The second technique is spray drying, which is carried out by spraying a dissolved mixture of an API and a coformer into a hot stream; the solvent thus evaporates and MCCs form.…”
Section: Solution-based MCC Preparation Methodsmentioning
confidence: 99%
“…The most commonly used technique for preparing phytochemical MCCs using the solution-based method is solvent evaporation (Katherine et al, 2018;Setyawan et al, 2018;Zaini et al, 2020b), in which the API and coformer are dissolved with a suitable solvent and the solvent is then allowed to evaporate slowly at room temperature (Kumar, 2018) . The second technique is spray drying, which is carried out by spraying a dissolved mixture of an API and a coformer into a hot stream; the solvent thus evaporates and MCCs form.…”
Section: Solution-based MCC Preparation Methodsmentioning
confidence: 99%
“…In another study, piperine cocrystal formation with succinic acid as coformer has been reported, with solubility and dissolution four and two times higher than that of intact piperine, respectively [17]. In general, improved solubility in salt and/or cocrystal were due to decreased crystallinity and intramolecular interactions in the crystal lattice, resulting in a decrease in crystal lattice energy and its enthalpy [14,17]. Particularly in the formation of piperine-succinic acid cocrystal, a channel motive structure is thought to be the main mechanism underlying the increase in piperine's solubility and dissolution [17].…”
Section: Derivatives and Analogue Synthesismentioning
confidence: 96%
“…Thermodynamic studies showed that the formed polymorph is a monotropic metastable crystalline form, which accounted for its increased solubility. Salt formation of piperine with saccharin has been reported, resulting in dissolution rate improvement [14]. The difference between pKa value of piperine (weak base pKa = 13.2) and saccharin (weak acid pKa = 1.6) allows the formation of salttype multicomponent crystals [15,16].…”
Section: Derivatives and Analogue Synthesismentioning
confidence: 99%
“…[16] Some efforts to increase the solubility and dissolution rate of piperine have been carried out, including the formation of a solid dispersion system, [17] inclusion complex formations, [18] nanosuspensions, [19] and the formation of multicomponent crystals with succinic acid, nicotinic acid, and saccharin. [20][21][22] One of the recent strategies for modifying the physicochemical properties of active pharmaceutical ingredients is the development of combined crystal engineering and nanotechnology techniques. Nano-cocrystal technology has emerged as an attractive strategy to further enhance the solubility and dissolution rate of poorly soluble drugs by reducing the crystal size to nanometer proportions (i. e., < 1000 nm).…”
Section: Introductionmentioning
confidence: 99%
“…To deal with problems related to the solubility and dissolution rate of active pharmaceutical ingredients, several methods have been developed to modify these active drug compounds, both physically and chemically [16] . Some efforts to increase the solubility and dissolution rate of piperine have been carried out, including the formation of a solid dispersion system, [17] inclusion complex formations, [18] nanosuspensions, [19] and the formation of multicomponent crystals with succinic acid, nicotinic acid, and saccharin [20–22] …”
Section: Introductionmentioning
confidence: 99%